KELISANAN DAN POLA PIKIR - Acep Iwan Saidi (Jurnal Sosioteknologi, 2011)
The term of orality is often understood in the narrow sense. It is often paired with the term of uteracy. Language actually contains other matters than merely sound and letters. The idea that language is human and vice versa is believed by the hermeneuticists. Verbal language is always regarded as less important than written language. However, each has its own strengths and characteristics with which each individual's thinking patter is constructed. Therefore, it is necessary that these two language types be treated equally.